2010
DOI: 10.1084/jem.20090849
|View full text |Cite
|
Sign up to set email alerts
|

TNF suppresses acute intestinal inflammation by inducing local glucocorticoid synthesis

Abstract: Although tumor necrosis factor (α) (TNF) exerts proinflammatory activities in a variety of diseases, including inflammatory bowel disease, there is increasing evidence for antiinflammatory actions of TNF. In contrast, glucocorticoids (GCs) are steroid hormones that suppress inflammation, at least in part by regulating the expression and action of TNF. We report that TNF induces extraadrenal production of immunoregulatory GCs in the intestinal mucosa during acute intestinal inflammation. The absence of TNF resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
171
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 151 publications
(185 citation statements)
references
References 32 publications
(56 reference statements)
11
171
0
3
Order By: Relevance
“…Although TNFα is considered clinically causative in IBD, mice deficient in TNFα exhibit enhanced intestinal inflammation during DSS colitis and 40% more deaths compared with no deaths in WT mice (28). Also, the absence of TNFα results in a lack of colonic glucocorticoid synthesis and there is exacerbation of DSS-induced colitis (29). TNFα-deficient mice also had increased infiltration of mucosal neutrophils and disruption of the epithelial cell layer (28).…”
Section: Protective Role For Tnfα In the Innate Response Of The Intesmentioning
confidence: 96%
“…Although TNFα is considered clinically causative in IBD, mice deficient in TNFα exhibit enhanced intestinal inflammation during DSS colitis and 40% more deaths compared with no deaths in WT mice (28). Also, the absence of TNFα results in a lack of colonic glucocorticoid synthesis and there is exacerbation of DSS-induced colitis (29). TNFα-deficient mice also had increased infiltration of mucosal neutrophils and disruption of the epithelial cell layer (28).…”
Section: Protective Role For Tnfα In the Innate Response Of The Intesmentioning
confidence: 96%
“…Locally produced GCs might also add to the overall effect (49). Accordingly, RU486, a known GC receptor antagonist, is capable of inducing a disruption of LPS tolerance in LPS-tolerized mice (50).…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, it has been reported that the synthesis of bioactive GCs is not restricted to the adrenal glands, but extends to other extra-adrenal sources such as the skin, intestine, thymus, brain, and vascular endothelium (82,83). In addition, it has been postulated that TNF␣ promotes local steroidogenesis by directly inducing steroidogenic enzymes in intestinal epithelial cells (84,85). Therefore we investigated whether TNF␣ stimulates steroidogenesis in other organs besides the adrenal glands and whether this results in the observed TNF␣-mediated GR reduction in Adx mice.…”
Section: Discussionmentioning
confidence: 99%